Afghanistan--state building, sustaining growth, and reducing poverty. (World Bank country study., 2005)
Afghanistan has come a long way since emerging from major conflict in late 2001. The economy has recovered strongly, growing by nearly 50% cumulatively in the last two years (not including drugs). Some three million internally and externally displaced Afghans have returned to their country. More than four million children, a third of them girls, are in school, and immunization campaigns have achieved considerable success. The Government has supported good economic performance by following prudent macroeconomic policies and it has made extraordinary efforts to develop key national programs and to revive social services like education and health. Nevertheless, Afghanistan remains one of the poorest countries in the world in terms of both per-capita incomes and social indicators, with large gender gaps. The difficult challenge of poverty reduction is made even more difficult by continuing insecurity, weak rule of law, and narcotics. Afghanistan - State Building, Sustaining Growth, and Reducing Poverty provides a greater understanding of the core challenges that lie ahead for Afghanistan and key priorities for national reconstruction. The Afghan economy has been shaped by more than two decades of debilitating conflict and has some very unusual features which this study analyzes. The authors argue that the country must break out of the vicious cycle that would keep it insecure, fragmented politically, weakly governed, poor, dominated by the illicit economy, and a hostage to the drug industry. The study presents key elements for a breakthrough in the next two years but the daunting agenda will require strong commitment, actions, and persistence on the part of the Government and robust support from the international community.